Assessing global COPD awareness with Google Trends. Issue 6 (27th June 2019) - Boehm, Anna; Pizzini, Alex; Sonnweber, Thomas; Loeffler-Ragg, Judith; Lamina, Claudia; Weiss, Guenter; Tancevski, Ivan
Although chronic obstructive pulmonary disease (COPD) prevalence and mortality rates rise continuously, patients often remain undiagnosed, probably due to a lack of disease-related awareness. The aim of this study was to quantify public interest in COPD by analysing the frequency of web queries via Google. Data from 2004 to 2018 were collected using the search engine query data analysis tool Google Trends. The relative search volume of the topic "chronic obstructive pulmonary disease" was compared with the relative search volume of nine topics representing the major causes of death in high-income countries according to the World Health Organization. Our analysis showed highest relative search volumes for the topics "diabetes mellitus", followed by "stroke" and "breast cancer". The topic "chronic obstructive pulmonary disease" ranked eighth and its relative search volume clearly displayed a seasonal variation, with peaks in the first and the fourth quarter of the year. This analysis reveals that COPD is highly under-represented in the public interest, while real-world prevalence constantly rises, indicating that there is still an urgent need to raise the levels of awareness for COPD. Google Trends provides us with an important tool to evaluate public interest related to COPD and associated respiratory diseases. COPD is highly under-represented in Google search queries compared with other frequent but "less preventable" diseases. http://bit.ly/2PAEwZW